Assessment of self-perceived oral health status, psychological well-being and life satisfaction among geriatric population - Bhuvana Durga Kolli; Srinivas Pachava; Devaki Talluri; Satya Madhuri Veligatla; Jhansi Patnala; Vishnu Kumar Selvaraj (Wolters Kluwer Medknow Publications, 2023)
Aims: This study aims to find out the association between self-perceived oral health status, psychological well-being and life satisfaction. Settings and Design: A cross-sectional study conducted on 400 geriatric people aged 60 years and above, residing in Tadikonda Mandal of Guntur district, Andhra Pradesh, India. Subjects and Methods: Self-perceived oral health was assessed through self-rating of oral health, speaking ability index, chewing capability index, and psychosocial impact scale oral health impact profile. Life satisfaction was assessed through single-item question, How satisfied with your life as a whole with 4 point Likert scale. Psychological well-being was assessed through two domains: Perceived life stress and general health, i.e., anxiety and depression. People who were mentally retarded, bedridden and who were not interested to participate in the study are excluded. Statistical Analysis Used: Chi-square, t-test, one way ANOVA test, poison regression analysis. Results: A poison regression model with perceived life stress as outcome, depicted that good self-rated oral health subjects had significantly lower perceived life stress scores (prevalence rate ratio [PRR] = 0.762; 0.649-0.894) than poor self-rated oral health subjects which is constant 1. When the outcome was changed to general health in the model, subjects who self-rated oral health as good have lower depression scores (PRR = 0.763; 0.667-0.873) than subjects, who self-rated oral health as poor which is kept constant 1. Conclusions: Poorer psychological well-being and lower life satisfaction are co-existing within the poor self-perceived oral health group of elderly, where poor self-rated oral health was found to be an important mediator of quality of life.